Efficient Implementation of Radar Imaging Techniques Including Time Gating Clutter Removal for Through the Walls Applications - Orlandino Testa; Stefano Pisa; Renato Cicchetti (IEEE Access)
Short-range radars are widely used for automotive applications, through-the-wall imaging and to monitor the elderly activity into their home. Given the relevance of such applications, some imaging algorithms are reformulated using a consistent formalism applied with a very efficient region-of-interest grid step. Moreover, to reduce the computation time, the numerical procedures are structured in such a way to employ fast Fourier transform or inverse fast Fourier transform algorithms whenever it results possible, while to reduce the artifact effects due to antenna and wall reflections, the time domain gating technique is implemented. The adoption of the combined technique (reconstruction algorithms and time gating) allows to remove the artifacts on both simulated and measured data with performances comparable with those of the background subtraction technique. The reported test cases evidence the ability of the considered algorithms to operate with different fractional bandwidth and with very fast execution times.